Implementasi Kebijakan Pengembangan Pariwisata Bone Bolango (Studi Kasus Pada Wisata Hiu Paus Botubarani) - Yakobu, Fauzia P. Pratiwi; Aneta, Yanti; Nani, Yacob Noho (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to understand and describe (1) How is the implementation oof the Bone Bolango tourism development policy, specifically in the botubarani whale shark tourism (2) Determining factors for the success of the implementation of Bone Bolango tourism development policy, particularly in botubarani whale shark tourism. The research employs qualitative with descriptive reaserch type. Data collection methods include observation, interviews, and documentation. Data analysis utilizes the Huberman model. This research also found thet implementing the Bone Bolango toutism development policy, particulary in Botubarani wahel shark tourism, has been effectively executed according to the planning in RIPPDA Number 2 of 2013. However, the govermenment should plan additional attractions for Botubarani whale shark tourism. The execution has followed the plans, but the local government should pay more attention to the facilities available at Botubarani whale shark tourism, and evaaluations are conducted every six months. However, challenges include the formation factor, where there is still a lack of specific information giving structures such as the Touris Information Center (TIC), anf the community has yet to fully exploit the potentials available within this tourism site, such as establishing seafood culinary businesses considering it is a marine/oceanic tourism site.